Bemberg. Women Filmmakers in Argentina, de Matt Losada - Tompkins, Cynthia Margarita (Imagofagia, 2021)
Sobre Matt Losada. Before Bemberg. Women Filmmakers in Argentina. New Brunswick: Rutgers Universiy Press, 2020. 184 pp. ISBN: 9781978814547